The Effectiveness of Communicative and Test-Focused Approaches in TOEFL® Preparation Classes - Achmad Farid; Adi Yusuf; Binti Qani’ah (Fakultas Komunikasi, Sastra, dan Bahasa, 2024)
This study investigates the effectiveness of the Communicative Approach and the Test-Focused Approach in TOEFL® preparation classes. Sixty-four students from Islamic Senior High School Madrasah Aliyah Al-Insan (pseudonym) in Jombang, East Java, Indonesia, were divided into two groups: one receiving instruction based on the Communicative Approach and the other on the Test-Focused Approach. Using a quasi-experimental design, pre-test and post-test scores were analyzed to measure improvements in TOEFL performance. The results showed significant score increases in both groups. The Communicative Approach group’s mean pre-test score of 456 improved to 483 post-intervention, while the Test-Focused Approach group’s mean score rose from 460 to 493. The paired sample t-test results indicated statistically significant improvements within each group, with p-values of 0.00 for the Communicative Approach and 0.00 for the Test-Focused Approach. Additionally, the independent sample t-test revealed that the Test-Focused Approach group performed significantly better than the Communicative Approach group post-intervention, with a p-value of 0.030. These findings align with existing theories on language learning and test preparation, suggesting that while communicative methods enhance overall language proficiency, test-focused strategies more effectively boost immediate test performance. The study concludes that integrating both approaches in TOEFL preparation programs can provide a balanced and comprehensive strategy, optimizing both language development and test readiness. Future research should explore the long-term effects of such integrated methods on students' language proficiency and academic success.